Association between air pollution and Pediatric Intensive Care Units hospitalization rates. (30th September 2020) - Comoretto, R; Gallo, E; Ocagli, H; Lorenzoni, G; Lanera, C; Martinato, M; Wolfler, A; Pettenazzo, A; Amigoni, A; Gregori, D
Abstract: Background: In the last years air pollution has been linked to an increased risk of several children respiratory pathologies, especially low respiratory tract infections. In more severe cases, the child could be hospitalized in Pediatric Intensive Care Unit (PICU). The present study aims to evaluate the association between the exposure to air pollution and (i) PICU admissions and (ii) hospitalization rates among children with a previous PICU admission. Methods: PICU admissions due to respiratory diseases were collected from 2010 to 2019 in Padua hospital (Italy) based on a large clinical Italian register. Furthermore, for subjects admitted in 2013, all subsequent hospitalizations have been tracked until 2019 from hospital discharge records. Environmental data were obtained from monitoring stations located within 20 km from the children residence. A conditional logistic regression based on a time-stratified case-crossover design will be performed to evaluate the association between hospital admissions and NO2, PM2.5 and PM10 in aerodynamic diameter. Results: The registry contains data about more than 30000 PICU admissions, of which around 30 % are of children under one year of age. An increased prevalence for respiratory diseases' admissions, from 18% in 2010 to 24% in 2019 can be observed. More than 400 children were admitted to Padua's PICU in 2013. In the following years, all these subjects experienced at least one hospitalization (median 2, [IQR 1-5]) for more than 2000 hospital admissions from 2014 up to 2019. Conclusions: Exposure of infants to air pollution could lead to more severe outcome as hospitalization as a result of a vulnerable lung condition that eases virus infections. This condition identifies a particularly frail population. With this approach, an association between air pollution and PICU admissions could be investigated in order to adopt public health policies aimed at safeguarding this frail population. Key messages: The study would detect an association between air pollution and hospital admissions as severe outcomes in infants and children. Furthermore, this is the first study that would assess if there is an association between these two factors in more frail subjects already hospitalized in a Pediatric Intensive Care Unit.